Strategic excellence and technological integration: Sustaining competitive advantage for private universities in Indonesia - Hidayah, Nurul; Nugroho, Lucky; Utami, Fransisca Listyaningsih (Edelweiss Applied Science and Technology, 2024)
The competition among private universities in Indonesia is intensifying, requiring institutions to establish a sustainable competitive advantage through the right strategies, strong vision and mission, and effective use of information technology. This study analyzes the influence of strategy, vision and mission, university rankings, and information technology on the sustainable competitive advantage of private universities. It also examines the moderating role of information technology in strengthening these relationships. Using a quantitative approach with a descriptive and causal design, data were collected from 204 respondents across private universities in Indonesia via a questionnaire. Analysis using Partial Least Squares (PLS) and SmartPLS software reveals that strategy, vision and mission, university rankings, and information technology significantly impact sustainable competitive advantage. Furthermore, information technology strengthens the influence of strategy, vision, and mission but does not moderate the relationship between university rankings and competitive advantage. These findings indicate that while information technology supports strategic implementation and the achievement of institutional vision and mission, its direct role in enhancing university rankings is limited. The study emphasizes the importance of formulating innovative, sustainable strategies and integrating information technology effectively to maintain competitiveness. Practical implications include the necessity of resource planning and investment in technology to achieve strategic objectives. This study contributes to the literature by exploring the moderating role of information technology in private universities, providing valuable insights for managers on leveraging technology to navigate competitive challenges and sustain growth.